The predictors of perforated appendicitis in the pediatric emergency department: A retrospective observational cohort study - Zlatan Zvizdic (9212371) (2021)
Objective Appendiceal perforation has significant effects on perioperative morbidity and postoperative outcome. The present study aimed to identify possible predictive factors associated with perforated appendicitis (PA) in children at admission in the emergency department (ED). Methods In this retrospective observational cohort study, consecutive medical records of children <18 years old with surgically and histopathologically confirmed acute appendicitis (AA) over three years (2013–2015) were analyzed. Patients were divided into two groups: PA and non-perforated appendicitis (NPA). The differences between the two groups and potential predictors of PA were explored using univariate and multivariate analyses. Results During the study period, 295 patients underwent an appendectomy and had confirmatory AA diagnoses. Ninety-two patients had a PA (31.2%). In the univariate analysis, male gender, vomiting, diarrhea, fever, elevated white blood cell count (WBC) levels, and high C-reactive protein (CRP) were identified as predictors of PA. In the multivariate analysis, male gender (odds ratio [OR]: 3.133; 95% confidence interval [CI]: 1.610–6.096); vomiting (OR: 2.346; 95% CI: 1.141–4.822); diarrhea (OR: 4.549; 95% CI: 1.850–11.181); fever (OR: 3.429; 95% CI: 1.765–6.663); elevated WBC (OR: 2.962; 95% CI: 1.491–5.884) and elevated CRP (OR: 3.061; 95% CI: 1.267–7.396) were variables that predicted the PA in children. Conclusion Our data indicate that several clinical and biochemical parameters can reliably distinguish between pediatric PA and NPA at admission in the emergency department. Other Information Published in: The American Journal of Emergency Medicine License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ajem.2021.06.028